Synthesis and Characterization of the Tetrafluoridochlorates(III) A[ClF4] (A = K, Rb, Cs). Issue 14 (6th March 2020) - Scheibe, Benjamin; Ivlev, Sergei I.; Karttunen, Antti J.; Kraus, Florian
Abstract : Single‐crystalline tetrafluoridochlorates(III) A [ClF4 ] ( A = K, Rb, Cs) were synthesized from solvolysis reactions of alkali metal fluorides in liquid chlorine trifluoride. The structures were examined by means of single‐crystal X‐ray diffraction. K[ClF4 ] crystallizes in the K[BrF4 ] structure type, whereas the Rb and Cs compounds crystallize in the Li[AuF4 ] structure type. The compounds were further characterized by Raman and IR spectroscopy. Solid‐state quantum‐chemical calculations with hybrid density functional methods reproduced the experimental structures and enabled the interpretation of the experimental Raman and IR spectra. Abstract : The reaction of ClF3 with alkali metal fluorides leads to the formation of tetrafluoridochlorates(III). The salts A [ClF4 ] ( A = K, Rb, Cs) were characterized by single‐crystal X‐ray diffraction, vibrational spectroscopy as well as quantum‐chemical solid‐state calculations.